Irisin a Novel Metabolic Biomarker: Present Knowledge and Future Directions - Ilse Yessabel Martinez Munoz; Eneida del Socorro Camarillo Romero; Jose de Jesus Garduno Garcia (International Journal of Endocrinology)
The rising prevalence of chronic diseases such as type 2 diabetes and cardiovascular diseases owing to fat mass excess has been described. In recent years, muscle function/dysfunction has become relevant in metabolic homeostasis. Irisin was described as an exercise-induced myokine. It is the product of type I membrane protein cleavage encoded by the fibronectin type III domain containing 5 (FNDC5) gene. The main beneficial function attributable to irisin is the change of subcutaneous and visceral adipose tissue into brown adipose tissue, with a consequential increase in thermogenesis. Irisin has also been described as a hormone that may have a key role in glucose homeostasis. The way the association of type 2 diabetes with obesity occurs is not fully understood. In recent years, the possible pathways through which irisin could interact with other organs such as the brain or bone have been described. The present paper intends to review the new findings and possible new directions in irisin research.